2021
DOI: 10.4271/04-14-02-0005
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Ignition Quality of Oxygenated Fuels Using Artificial Neural Networks

Abstract: Artificial intelligence based computing systems like artificial neural networks (ANN) have recently found increasing applications in predicting complex chemical phenomena like combustion properties. The present work deals with the development of an ANN model which can predict the derived cetane number (DCN) of oxygenated fuels containing alcohol and ether functionalities. Experimental DCN's of 499 fuels comprising of 116 pure compounds, 222 pure compound blends, and 159 real fuel blends were used as the datase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 108 publications
(192 reference statements)
1
5
0
Order By: Relevance
“…This shows the ability of ANNbased models to predict complex chemical phenomena, such as sooting propensity. This also supports the functional group-based approach employed here, which reiterates the ability of the functional groups to predict fuel properties, as previously demonstrated for cetane number [47,48] and octane number [44]. Another advantage of the functional group approach is the ability to predict the YSI of real fuels, which most other models reported in the literature are not designed to do.…”
Section: Ann Modelsupporting
confidence: 86%
See 2 more Smart Citations
“…This shows the ability of ANNbased models to predict complex chemical phenomena, such as sooting propensity. This also supports the functional group-based approach employed here, which reiterates the ability of the functional groups to predict fuel properties, as previously demonstrated for cetane number [47,48] and octane number [44]. Another advantage of the functional group approach is the ability to predict the YSI of real fuels, which most other models reported in the literature are not designed to do.…”
Section: Ann Modelsupporting
confidence: 86%
“…A number of parameters, such as batch size, epochs, number of hidden layers, and number of neurons in each hidden layer, were optimized to yield the final ANN model. Nearly 260 iterations were carried out and the best performance was ob- ously demonstrated for cetane number [47,48] and octane number [44]. Another ad-vantage of the functional group approach is the ability to predict the YSI of real fuels, which most other models reported in the literature are not designed to do.…”
Section: Ann Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Petroleum gasoline is composed of paraffin, olefins, naphthene, and aromatic compounds that can be disassembled into a finite number of functional groups which define the fuel’s properties. The functional groups in fuel have been used to predict the cetane number of diesel fuel and the sooting propensity of a wide class of neat compounds and also to formulate surrogates for gasoline, diesel, and jet fuels. Along with functional groups, two additional structural parameters called branching index (BI) and molecular weight (MW) have been included as input features in the ANN model. After each generated mixture is converted into the input features (i.e., functional groups, BI and MW), the ANN model predicts the RON and MON of each.…”
Section: Computational Methodologymentioning
confidence: 99%
“…As is the case with RON and MON measurements, experimental measurement of CN/DCN is expensive, and there are multiple studies [33,38,39] reported in the literature that have developed models for CN/DCN prediction. Recently, an artificial neural network-based technique [40] was developed for predicting of the DCN of fuels containing oxygenated classes like alcohols and ethers by using the functional groups as input parameters. The DCN prediction model was developed by using 499 fuels, and the model consisted of two hidden layers with 442 nodes in the first layer followed by 290 nodes in the second.…”
Section: Property Prediction 41 Octane Number (On)mentioning
confidence: 99%